2011
DOI: 10.1128/aem.01920-10
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Adhesin Gene Sequences in, and Biofilm Formation by, O157 and Non-O157 Shiga Toxin-ProducingEscherichia coliStrains Isolated from Different Sources

Abstract: Biofilm formation by Shiga toxin-producing Escherichia coli (STEC) has been associated with the expression of different adhesins (type 1 fimbria, curli, Ag43, Cah, and EhaA). In this study, biofilm formation and the presence of adhesin-related gene sequences were determined by PCR in 18 O157 strains and 33 non-O157 strains isolated from different sources (human, animal, food, and water). The expression of different adhesins was also assessed by reverse transcription-PCR (RT-PCR), Congo red agar plates, and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
44
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 38 publications
11
44
0
7
Order By: Relevance
“…The first set of primers amplified the passengerencoding domain sequence (named eha ␣ ) where nucleotide divergences have been described. The other set of primers amplified the translocationencoding domain sequence (named eha ␤ ), which is highly conserved (8,18,28).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first set of primers amplified the passengerencoding domain sequence (named eha ␣ ) where nucleotide divergences have been described. The other set of primers amplified the translocationencoding domain sequence (named eha ␤ ), which is highly conserved (8,18,28).…”
Section: Methodsmentioning
confidence: 99%
“…The biofilm-forming ability of STEC has been investigated under different conditions, using different STEC isolates representing different serotypes and origins (6)(7)(8). Biofilm formation by STEC may be regarded as a survival strategy for this bacterium (9)(10)(11)(12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This observation has led to naming the proteins calcium-binding antigen 43 homologous or Cah. The recent evaluation of cah genes in a STEC collection found that the cah gene was present in 17 of 18 STEC O157:H7 strains (94%) and 6 of 33 STEC non-O157 strains (18%) (10). Expression of Cah on E. coli DH5␣ produced an autoaggregation phenotype, absent when the cah gene is inactivated, indicating that Cah promotes bacterium-to-bacterium interaction (95).…”
Section: Stec Autotransportersmentioning
confidence: 99%